2018
DOI: 10.1002/ppul.24204
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of lung function in children with parapneumonic empyema

Abstract: Rationale: Prospective studies that evaluated the outcome of childhood empyema are limited.Objective: To compare the outcome of pulmonary function in children with empyema.Patients and Methods: Children discharged with a diagnosis of empyema underwent a longitudinal study including measurement of pulmonary function and radiographic imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…33 Since lung ultrasound offers several benefits over chest CT, such as wide availability, no need for sedation, low cost, and no radiation exposure, it has been recommended in children with complicated pneumonia. 34 All patients described by Gross et al 10 had a complete radiographic resolution in the follow-up, thus confirming the results of our 35 and other authors' 7-9 studies.…”
supporting
confidence: 90%
“…33 Since lung ultrasound offers several benefits over chest CT, such as wide availability, no need for sedation, low cost, and no radiation exposure, it has been recommended in children with complicated pneumonia. 34 All patients described by Gross et al 10 had a complete radiographic resolution in the follow-up, thus confirming the results of our 35 and other authors' 7-9 studies.…”
supporting
confidence: 90%
“…The proportion of cases of empyema caused by Streptococcus pneumoniae was relatively low compared to previous studies. [17][18][19] Lin et al 20 Pseudomonas aeruginosa was the third most common cause of empyema in this study. This is similar to the findings of a recent study conducted in Iran, which found a prevalence of Pseudomonas aeruginosa of 18.1% among 105 children with empyema.…”
Section: Fig 3 Study Flow Chartmentioning
confidence: 48%
“…They have lower rates of needing rescue surgical therapy, and their long-term outcomes are almost always complete recovery with a near-zero rate of mortality. [25][26][27] In the current study, this difference was further amplified by the fact that we specifically excluded children with serious long-term comorbidities. Participants in the adult trial had a variety of comorbidities, and the mortality rate was 11% after 12 months of follow-up.…”
Section: Discussionmentioning
confidence: 93%